Obstacles in entrepreneurship among graduates: a comparative study between UiTM Pahang and UiTM Melaka / Musramaini Mustapha, Ilyani Azer and Siti Aishah Mohamad - Mustapha, Musramaini; Azer, Ilyani; Mohamad, Siti Aishah (Faculty of Administrative Science and Policy Studies, 2012)
Entrepreneurship is one of the professions that promise a very bright future to graduates if they successfully participate in any kinds of potential sector. Currently, Ministry of Higher Education encourages entrepreneurship development for graduates from all universities in Malaysia. Due to that reason, universities urge to handle as much as entrepreneurship activities in order to let graduates experience the real situation as to become a real entrepreneur in the future. With all entrepreneurship development program conducted, it is very minimum study to focus on barriers toward entrepreneurship from perspectives of graduates. In this study, the main objective is to highlight the obstacles in entrepreneurship among graduates. The result indicate that graduates’ perspectives of lack of savings, lack of assets for collateral and difficulty in obtaining bank finance are the main three obstacles in entrepreneurship. The difference obstacle factor in entrepreneurship between genders shows different factors toward selected obstacles in entrepreneurship. Overall, both male and female perceived to be agreed on certain factors that is mainly financial obstacles.